Proceeding of Fourth International Conference on Spoken Language Processing. ICSLP '96
DOI: 10.1109/icslp.1996.607942
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the McGurk effect: implications for theories of speech perception

Abstract: Studies of the McGurk effect demonstrate that observers integrate auditory information with visual information from a talker's face during speech perception. The findings from these studies pose challenges for theories of speech perception that must account for how and why the auditory and visual information are integrated. One theoretical issue concerns the objects of speech perception. Some researchers claim that the objects of speech perception are articulatory gestures while others argue that the objects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…If so, why are visual cues combined with auditory cues when auditory cues are available to accurately understand speech? These psycholinguists theorized the purpose of speech perception was whether they are auditory related or articulatory related in nature (Green, 1996). Cognitive psychologists also proposed auditory and articulatory theories to explain auditory-visual integration in speech perception.…”
Section: Basic Theories For Auditory-visual Integration In Speech Permentioning
confidence: 99%
See 1 more Smart Citation
“…If so, why are visual cues combined with auditory cues when auditory cues are available to accurately understand speech? These psycholinguists theorized the purpose of speech perception was whether they are auditory related or articulatory related in nature (Green, 1996). Cognitive psychologists also proposed auditory and articulatory theories to explain auditory-visual integration in speech perception.…”
Section: Basic Theories For Auditory-visual Integration In Speech Permentioning
confidence: 99%
“…Thai language contains the phoneme /ŋ/ in both word-initial and word-final positions, but English does not contain the phoneme /ŋ/ in word-initial position. Thus, Burnham (1998) hypothesized that English participants would respond more with /n/ in the initial position than in the final position due to visual ambiguity of /ŋ/ (visual /ŋ/ looks like visual /n/) and their language experience (Burnham, 1998 Green (1996) concluded that the McGurk effect occurs phonetically (i.e., vowel context) not phonologically (listener's language). The cross-language studies revealed that this auditory-visual integration occurs at an earlier phonetic level of processing and that integration is affected by phonetic factors (Green, 1996).…”
Section: Audio-visual Integration In Speech Perceptionmentioning
confidence: 99%
“…Other related studies followed the initial description of the McGurk illusion [e.g., 2,3], and several different theories were offered [4,5,6]. Green [2], in this session, presents an overview of research on the McGurk illusion.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Green [2], in this session, presents an overview of research on the McGurk illusion. The paper by Sekiyama et al [3], in this session, shows that the illusion is sensitive to native language, acoustic quality, language proficiency, and cultural factors.…”
Section: Historical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation